Influence of local economic development strategic leaders on the formulation of the integrated development plan, Makana Municipality, Eastern Cape - Nonxuba, Mnweba McNair (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
The influence of local economic development strategic leaders on how Integrated Development Plans (IDP) are developed is critical to gain insights into strategic planning directed towards economically developing municipalities. Concisely, the aim of this qualitative study was to gain a multiple understanding of how LED strategic leaders, namely managers of the LED directorate and sub-directorates at Makana local municipality influenced the IDP formulation. The fact that these LED strategic leaders, 'make consequential or strategic decisions' suggests that their decisions have an influence on the IDP formulation. Thus, the key research question in this study was: How do LED strategic leaders at Makana local municipality influence the formulation of the IDP at this municipality? This qualitative research used purposive sampling of incidents upheld by LED Strategic leaders. A total of ten in-depth and semi-structured interviews were conducted with four LED strategic leaders regarding incidents of their perceived influence on the formulation of the Integrated Development Plan at Makana. The interviews were in-depth in order to gain a rich understanding of their perspectives of reality. As the number of LED strategic leaders was already very small, all the four leaders at Makana participated in this study. Interview data was transcribed and analyzed using open coding and constant comparison. Member check was conducted to enhance confirmability of the findings of this study. Findings indicate that LED strategic leaders perceived their influence on the formulation of the IDP Makana municipality in four varied ways. Predominantly, LED strategic leaders commonly perceived that they had influence in setting evidence-driven direction, and searching for fitness of activities and issues with LED strategy. Thereafter, the other ways in which these LED strategic leaders perceived how they influenced the IDP formulation involve the facilitation of clarity and local relevance of LED mandates, and finally the integration of multiple economic voices of stakeholders. This demonstrates that LED strategic leaders at Makana emphasize proactively managing strategy process rather than content in terms of identifying key opportunities and major economic drivers in the local milieu. Instead, they perceived their influence as characterized by enhancing compliance with bringing the process of municipal strategy formulation closer to stakeholders. Implications of these findings are highlighted.
Keywords: Local Economic Development (Programme); Community development -- South Africa -- Grahamstown; Municipal government -- South Africa -- Grahamstown; Strategic planning -- South Africa -- Grahamstown; Grahamstown (South Africa) -- Economic conditions -- 21st century; South Africa -- Politics and government